Aspects of pulse oximetry screening for critical congenital heart defects: when, how and why?. Issue 2 (14th September 2015) - Narayen, Ilona C; Blom, Nico A; Ewer, Andrew K; Vento, Maximo; Manzoni, Paolo; te Pas, Arjan B
Abstract : Pulse oximetry (PO) screening for critical congenital heart defects (CCHD) has been studied extensively and is being increasingly implemented worldwide. This review provides an overview of all aspects of PO screening that need to be considered when introducing this methodology. PO screening for CCHD is effective, simple, quick, reliable, cost-effective and does not lead to extra burden for parents and caregivers. Test accuracy can be influenced by targets definition, gestational age, timing of screening and antenatal detection of CCHD. Early screening can lead to more false positive screenings, but has the potential to detect significant pathology earlier. There is no apparent difference in accuracy between screening with post-ductal measurements only, compared with screening using pre-ductal and post-ductal measurements. However, adding pre-ductal measurements identifies cases of CCHD which would have been missed by post-ductal screening. Screening at higher altitudes leads to more false positives. Important non-cardiac pathology is found in 35–74% of false positives in large studies. Screening is feasible in neonatal intensive care units and out-of-hospital births. Training caregivers, simplifying the algorithm and using computer-based interpretation tools can improve the quality of the screening. Caregivers need to consider all aspects of screening to enable them to choose an optimal protocol for implementation of CCHD screening in their specific setting.